2007
DOI: 10.1073/pnas.0705147104
|View full text |Cite
|
Sign up to set email alerts
|

CERK1, a LysM receptor kinase, is essential for chitin elicitor signaling in Arabidopsis

Abstract: Chitin is a major component of fungal cell walls and serves as a microbe-associated molecular pattern (MAMP) for the detection of various potential pathogens in innate immune systems of both plants and animals. We recently showed that chitin elicitor-binding protein (CEBiP), plasma membrane glycoprotein with LysM motifs, functions as a cell surface receptor for chitin elicitor in rice. The predicted structure of CEBiP does not contain any intracellular domains, suggesting that an additional component(s) is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
1,100
3
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,235 publications
(1,148 citation statements)
references
References 33 publications
26
1,100
3
19
Order By: Relevance
“…In the Arabidopsis genome, five chitin elicitor LysM receptor-like kinase 1 (LysM RLKs) are encoded, of which only one was implicated in chitin detection and named AtCERK1 for chitin elicitor receptor kinase 1 or LysM RLK1 (Miya et al 2007; Wan et al 2008). Structurally, AtCERK1, an RLK, is composed of a transmembrane domain, three tandem LysMs in its ectodomain and an intracellular serine/threonine kinase domain (Miya et al 2007; Wan et al 2008) in Arabidopsis .…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Arabidopsis genome, five chitin elicitor LysM receptor-like kinase 1 (LysM RLKs) are encoded, of which only one was implicated in chitin detection and named AtCERK1 for chitin elicitor receptor kinase 1 or LysM RLK1 (Miya et al 2007; Wan et al 2008). Structurally, AtCERK1, an RLK, is composed of a transmembrane domain, three tandem LysMs in its ectodomain and an intracellular serine/threonine kinase domain (Miya et al 2007; Wan et al 2008) in Arabidopsis .…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
“…Structurally, AtCERK1, an RLK, is composed of a transmembrane domain, three tandem LysMs in its ectodomain and an intracellular serine/threonine kinase domain (Miya et al 2007; Wan et al 2008) in Arabidopsis . Chitin-induced AtCERK1 homodimerisation has been proved to be necessary for its activation (Liu et al 2012).…”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has revealed that, like PBS1, BIK1 and several PBS1-like (PBL) RLCKs are also substrates of the bacterial AvrPphB protease effector . This discovery and other work suggests that a bacterial effector can suppress PAMP-triggered immunity in plants by cleaving RLCKs known (BIK1) or proposed (PBL1, PBL2) to positively interact with RLKs that bind PAMPs, including FLS2, CHITIN ELICITOR RECEPTOR KINASE1, and the EF-Tu RE-CEPTOR (Zipfel et al, 2006;Miya et al, 2007;Zhang et al, 2010). During effector-triggered immunity, another RLCK, RPM1-INDUCED PROTEIN KINASE (RIPK), is involved in activating the NB-LRR protein RPM1 (Liu et al, 2011).…”
mentioning
confidence: 95%